Participation in the Development of MICE Tourism as a Destination Tourism Product in Lombok - Putu Agung Prianta; Dinar Sukma Pramesti (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to analyze the role of participation in the development of MICE tourism in Lombok, identify the factors affecting its effectiveness, and formulate development strategies. Method: This study employed a qualitative approach through observation, interviews, and literature review, using descriptive analysis based on participation theory, stakeholder theory, and destination competitiveness theory. Result: The findings indicate that participation has involved various stakeholders; however, it has not been optimal and remains dominated by the government and private sector. Community participation tends to be in the form of tokenism and induced participation. The main barriers include power imbalances, limited access to information, low community capacity, weak coordination, and a top-down approach. Development strategies need to be implemented in an integrated manner through strengthening collaboration, inclusive participation, infrastructure improvement, and the utilization of technology to enhance destination competitiveness and sustainability. Contribution: This study contributes theoretically by strengthening the discourse on stakeholder participation in MICE tourism development, and practically by providing recommendations for collaborative, inclusive, and sustainable strategies to enhance the competitiveness of Lombok as a destination.